MANAJEMEN PONDOK PESANTREN AULIA CENDEKIA PALEMBANG UNTUK MENINGKATKAN KETERAMPILAN SANTRI DALAM BERDAKWAH - Nuha Nabila Aswari; Nuraida Nuraida; Nazarmanto Nazarmanto; Nurseri Hasnah Nasution (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
The purpose of this study was to find out the management of the Aulia Cendekia Palembang Islamic boarding school, and the efforts made by the Aulia Cendekia Paalembang Islamic boarding school to improve the skills of the Santri in preaching. This research is a qualitative research with a descriptive approach. The types of data sources for this research are primary and secondary data sources, the primary data sources in this study are the leadership of the Islamic boarding school, the chairman of the Aulia Cendekia Palembang Islamic boarding school dormitory, Ustadz / Ustadzah da'wah supervisors, students and female students of class XII MA, and administrators related to preaching coaches . Data collection techniques in this study used interviews, observation and documentation and data analysis in this study used data reduction, data presentation, and drawing conclusions. The results of this study are that the Aulia Cendekia Islamic boarding school in Palembang has implemented management principles by implementing daily activities for each student and female student, at the Aulia Cendekia Islamic boarding school there are also planning and evaluation to make it better, besides that there are also economic aspects, aspects education, aspects of da'wah, and aspects in the pesantren environment. There is a program for the XII MA, namely the ni'hai program, there are also weekly muhadoroh and monthly muhadoroh kubro. Da'wah training is very important for students. The efforts made by Islamic boarding schools are so that students and female students can appear in society, following the best female students and female students for competitions in order to train their abilities. self-quality, allows them to appear in society, and can potentially be part of the da'wah. The inhibiting factor is the lack of library facilities so that students and female students do not look for materials for da'wah training, nor is the motivation of human resources to take part in preaching training.